A 4-Point Block Method For Solving Higher Order Ordinary Differential Equations Directly - Nazreen, Waeleh; Zanariah, Abdul Majid (Hindawi Publishing Corporation, 2016)
An alternative block method for solving fifth-order initial value problems (IVPs) is proposed with an adaptive strategy of implementing variable step size. The derived method is designed to compute four solutions simultaneously without reducing the problem to a system of first-order IVPs. To validate the proposed method, the consistency and zero stability are also discussed. The improved performance of the developed method is demonstrated by comparing it with the existing methods and the results showed that the 4-point block method is suitable for solving fifth-order IVPs.